Contrasting Cross-Sectional and Longitudinal Early School Leaver Rates in Canada - Timmons, Vianne; Ostridge, Randy (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2009)
AbstractData analysis is critical to educational planning. Determining the number of school leavers is crucial for a school board when planning for interventions and supports. In researching the number of early school leavers in the province of Prince Edward Island, the method in which the data were reported affected the rates. Two critical considerations should be looked at when reporting or analyzing school leaver rates: the definition of a school leaver, and whether the data collected are cross-sectional or longitudinal. This paper explores these two elements.